Enhanced Intrarenal Oxidative Stress and Angiotensinogen in IgA Nephropathy Patients - Kobori, Hiroyuki (2007)
This study was performed to determine whether immunoreactivity of intrarenal hemeoxygenase-1 and angiotensinogen are increased in IgA nephropathy (IgAN) patients. Hemeoxygenase-1 and angiotensinogen immunoreactivity were determined by immunohistochemistry robot system in renal specimens from 39 patients with IgAN. Normal portions of surgically resected kidney served as controls. IgAN patients showed moderate proteinuria (1.1+/−0.2 g/day); however, the control group did not show any proteinuria. Immunoreactivity of intrarenal hemeoxygenase-1 and angiotensinogen in IgAN were significantly increased compared to normal kidneys (2.42+/−0.42 vs 1.00+/−0.26 for hemeoxygenase-1 and 4.05+/−0.40 vs 1.00+/−0.21 for angiotensinogen, arbitrary unit). Even though these IgAN patients did not show massive renal damage, hemeoxygenase-1 and angiotensinogen immunoreactivity were increased in these patients at this time point. These data suggest that activated intrarenal reactive oxygen species-angiotensinogen axis plays some roles in development of IgAN at the early stage and will provide supportive foundation of effectiveness of the renin-angiotensin system blockade in IgAN.